Evidence for horizontal gene transfer, gene duplication and genetic variation as driving forces of the diversity of haemolytic phenotypes in Photobacterium damselae subsp. damselae - Rivas, Amable; Labella Vera, Alejandro Manuel; Borrego, Juan José; Lemos, Manuel; Osorio, Carlos (Oxford Academic, 2014)
Photobacterium damselae subsp. damselae, a marine bacterium that causes infections in marine animals and in humans, produces up to three different haemolysins involved in virulence, which include the pPHDD1 plasmidencoded damselysin (Dly) and HlyApl, and the chromosome-encoded HlyAch. We screened 45 isolates from different origins, and found a correlation between their haemolytic phenotypes and the differential haemolysin gene content. All highly and medium haemolytic strains harboured pPHDD1, with amino acid substitutions in HlyApl and HlyAch being the cause of the medium haemolytic phenotypes in some pPHDD1-harbouring strains. Weakly haemolytic strains contained only hlyAch, whereas nonhaemolytic isolates, in addition to lacking pPHDD1, either lacked hlyAch or contained a hlyAch pseudogene. Sequence analysis of the genomic context of hlyAch uncovered an unexpected genetic diversity, suggesting that hlyAch is located in an unstable chromosomal region. Phylogenetic analysis suggested that hlyApl and hlyAch originated by gene duplication within P. damselae subsp. damselae following acquisition by horizontal transfer. These observations together with the differential distribution of pPHDD1 plasmid among strains suggest that horizontal gene transfer has played a main role in shaping the haemolysin gene baggage in this pathogen.
Keywords: Bacterias marinas; Haemolysin; HlyA; Damselysin; Dly; Vibriosis; Vibrio damsela